33 Development of an intervention to support lung cancer patients and their clinicians when considering systematic anti-cancer therapy: the pact study, a prospective multi-centre multi-methods five-stage qualitative study. Issue 3 (1st September 2018) - Nelson, Annmarie; Byrne, Anthony; Sivell, Stephanie; Longo, Mirella; Noble, Simon; Lester, Jason; Anagnostou, Despina; Sampson, Catherine
Abstract : Background: The NHS aspires to place patients' needs wishes and preferences at the heart of a clinical decision-making; however it is not clear how this can be routinely implemented. One example is the patient clinical care pathway for patients diagnosed with advanced non-small cell lung cancer (NSCLC) where there may be misunderstanding of the extent of disease prognosis and aims of treatment. Aim: To understand how treatment decisions are made for NSCLC patients and map the decisions pathway. Methodology: PACT is a prospective multi-centre multi-methods five-stage qualitative study. Non-participant observation of MDT meetings (n=12) determined patients' allocation to treatment. Non-participant observation of patient-clinician consultations (n=14) explored communication of treatment options and decision-making. Interviews with patients/companions and clinicians (n=27) explored perception of treatment options and involvement in decision-making. Mediated discourse thematic framework and narrative analysis were used to analyse the data. An expert consensus meeting (n=33) finalised the content and format of a proposed intervention. Results: For NSCLC patients decision making was a process rather than a single event. Patients' priorities and preferences were not routinely or intrinsically part of the clinical pathway and arose according to the skills/attitudes of the clinician and the confidence/awareness of the patient. The interviews illustrate the uncertainty for patients around treatment considerations and highlighted the importance of knowing patients' priorities and preferences. Conclusion: Current pathway for NSCLC patients focuses on clinical management at the expense of patient-centred care. However clinicians' attitude towards hope for patients with non-curative diagnosis is instrumental to any process change.